(untitled) (International Congress on Economics, Management and Business Studies, 2026)
The safe operation of storage tanks at hazardous industrial facilities depends on the ability to determine their actual technical condition and predict possible changes during long-term operation. This article analyzes the application of comprehensive technical diagnostics for evaluating the condition of storage tanks and determining their remaining service life. The study considers the combined influence of corrosion damage, welded joint condition, metal thickness reduction, and operational factors affecting the reliability of tank structures. The study confirms that regular technical inspection and data-based assessment methods help identify critical changes in the condition of storage tanks at an early stage. This approach reduces the risk of unexpected failures and provides a scientific basis for planning maintenance and repair activities.